In Vitro Screening of Falcataria moluccana (Miq.) with Gall Rust (Uromycladium tepperianum (Sacc.) Filtrate as Media Selection - Asri Insiana Putri; Mohammad Na'iem; Sapto Indrioko; Sri Rahayu; Ari Indrianto (Indonesian Journal of Biotechnology, 2014)
In vitro screening of Falcataria moluccana (Miq.) was conducted by tissue culture method. Seeds fromtwo different site of community forest, 400 m (S1) and 800 m (S2) above sea level, were used as material.Double concentration of MS (Murashige & Skoog, 1962) with 40 mg/l gall rust (Uromycladium tepperianum(Sacc.) fi ltrate were used for media selection. The results of this research showed that 66 % axenic plantlets invitro from S1 and 27 % from S2 were still survived after 3 months incubation without subculture. The meanof fresh weight (2. 21 ± 0. 26 g) and dry weight (1. 97 ± 0. 12 g) from S1 plantlets lower than the mean of freshweight (2. 87 ± 0,18 g) and dry weight (2. 16 ± 0. 14 g) from S2 plantlets. Qualitative of terpenes, saponins andquantitative of total phenolics were analyzed from those gall rust extract, as source of fi ltrate media, attackedand un-attacked of F. moluccana. They all qualitatively have capability to produce terpenoid and saponin. Itis notice that U. tepperianum, un-cultured pathogen, contain of those compound that may play a role as codeterminantsof pathogenecity. While the highest total phenolic compound were contained in gall rust extract(2. 35 %), followed by attacked F. moluccana branches (1. 18 %) and un-attacked F. moluccana branches (0. 44%). This indicated that phenolic compound in gall rust has higher activity as a response of F. moluccana to U.tepperianum pathogen pressures and result of this study suggest the great value of gall rust fi ltrate for use asmedia selection in vitro.